2019
DOI: 10.1111/nph.15690
|View full text |Cite
|
Sign up to set email alerts
|

Protein and metabolite composition of Arabidopsis stress granules

Abstract: Summary Stress granules (SGs) are evolutionary conserved aggregates of proteins and untranslated mRNAs formed in response to stress. Despite their importance for stress adaptation, no complete proteome composition has been reported for plant SGs. In this study, we addressed the existing gap. Importantly, we also provide evidence for metabolite sequestration within the SGs. To isolate SGs we used Arabidopsis seedlings expressing green fluorescent protein (GFP) fusion of the SGs marker protein, Rbp47b, and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 56 publications
(117 reference statements)
9
150
0
Order By: Relevance
“…Similar results were reported for other plant proteins such as the polyadenylated (poly(A)+) mRNA binding protein PAB-2 [7] and the VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 [36], which in normal conditions localize to the cytoplasm and the nucleus, and are translocated to stress granules upon stress. However, despite the fact that ArathEULS3 transcript levels are known to be upregulated in response to drought stress the ArathEULS3 protein was not identified in the proteome of heat/dark treated plants [10] nor was it identified when examining the changes in RNA-binding proteome under drought stress conditions [9,37]. This might be explained by the fact that the proteome of the stress granules might change depending on the nature and severity of the stress conditions as well as the developmental stage of the plant [1].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar results were reported for other plant proteins such as the polyadenylated (poly(A)+) mRNA binding protein PAB-2 [7] and the VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 [36], which in normal conditions localize to the cytoplasm and the nucleus, and are translocated to stress granules upon stress. However, despite the fact that ArathEULS3 transcript levels are known to be upregulated in response to drought stress the ArathEULS3 protein was not identified in the proteome of heat/dark treated plants [10] nor was it identified when examining the changes in RNA-binding proteome under drought stress conditions [9,37]. This might be explained by the fact that the proteome of the stress granules might change depending on the nature and severity of the stress conditions as well as the developmental stage of the plant [1].…”
Section: Discussionmentioning
confidence: 93%
“…This might be explained by the fact that the proteome of the stress granules might change depending on the nature and severity of the stress conditions as well as the developmental stage of the plant [1]. Additionally the stress granules proteome analysis revealed elongation factors or chaperons, the presence of stress-related proteins such as receptors, kinases, and transcriptional regulators next to the predicted stress granule components like RNA-binding proteins [10]. Considering the stress-responsive nature of ArathEULS3, more proteomic analyses performed under different stress conditions will help to confirm the presence of ArathEULS3 protein in stress granules.…”
Section: Discussionmentioning
confidence: 99%
“…While the protein components of SGs and siRNA bodies in plants are relatively well known 56 , the RNA composition of such cytoplasmic compartments are poorly understood. Studies in human and yeast have shown that transcriptome of cytoplasmic RNA granules are associated with strong translational repression 23,25,57,58 .…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of cytoplasmic bodies was carried out by employing the SG enrichment methods reported previously 25,56,59 . Briefly, 2 g of samples was ground with a precooled mortar and pestle in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…MCs of plants and other eukaryotes contain overlapping sets of proteins, indicating a common function in eukaryotic metabolism. For example, stress granules, small cytoplasmic MCs that form upon a variety of stresses contain RNA, translation initiation factors, RNA-binding, and other proteins [75,76]. Curiously, also components of the cell cycle regulation machinery (see paragraph below), such as cyclin-dependent kinases localize to stress granules in both plant and human cells [76,77].…”
Section: Protein Disorder As a Driving Force For Liquid-liquid Phase mentioning
confidence: 99%